Real-time hybrid experiments with Newmark integration, MCSmd outer-loop control and multi-tasking strategies. - Bonnet, P. A.
Real-time hybrid testing is a promising technique for experimental structural dynamics, in which the structure under consideration is split into a physical test of key components and a numerical model of the remainder. The physical test and numerical analysis proceed in parallel, in real time, enabling testing of critical elements at large scale and at the correct loading rate. To date most real-time hybrid tests have been restricted to simple configurations and have used approximate delay compensation schemes. This paper describes a real-time hybrid testing approach in which non-linearity is permitted in both the physical and numerical models, and in which multiple interfaces between physical and numerical substructures can be accommodated, even when this results in very stiff coupling between actuators. This is achieved using a Newmark explicit numerical solver, an advanced adaptive controller known as MCSmd and a multi-tasking strategy. The approach is evaluated through a series of experiments on discrete mass?spring systems.
Keywords: Real-time testing; Substructuring; Adaptive control